EFEK PENGGUNAAN MEDIA SOSIAL TERHADAP PRESTASI BELAJAR MAHASISWA - Oktiana Rahmawati, Riska Delia Br Pelawi, Royanatul Fitri (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Social media use among college students has become a widespread phenomenon. Social media offers various benefits such as ease of communication, fast access to information, and a platform for sharing ideas. However, excessive use can negatively impact academic performance. This research aims to examine the effect of using social media on student learning achievement. The method used is literature study and secondary data analysis from various previous studies. The research results show that there is a significant relationship between social media use and academic achievement, both positive and negative depending on students' usage patterns and self-control